The Educational Significance of the Qu'ranic Dialogue to Young Muslims in the West - Ahmed Mohammed Al khalidi (Perhimpunan Intelektual Muslim Indonesia, 2022)
This study sheds light on the ethical and social difficulties young Muslims face in the West. It aims to help Young Muslims fit socially without sacrificing their religion's principles, acquire Qu'ranic teachings and guidance, and assimilate Islamic principles and moral values that help them lead a righteous life. It attempts to achieve that by exposing young Muslims to the Qu'ranic educational significances and lessons and the moral values and Islamic principles derived from two types of Qu'ranic dialogue: the exchange dialogue and the speech dialogue. It seeks to develop a plan that enhances acquisition of ample Qu'ranic knowledge and guidance, assimilation of Qu'ranic ethical conducts, Islamic codes and social morals. It also seeks to provide Young Muslims with Qu’ranic teachings that strengthen their faith and immunity against non-Muslim passive social influences. As well, it helps Young Muslims refute the false claims about Islam. Moreover, this study recommends educationalists to help young Muslims eliminate indifference toward their religion, foster trust in themselves toward their Islamic identity and transfer this study into educational programs, and conduct further study from another perspective. Finally, this study concludes the abolition of young Muslims' ignorance of their religion and fostering the pure Islamic doctrine in their hearts.